Analisis Dan Perancangan Sistem Informasi Layanan Perizinan Dan Monitoring Berkas Pada Pelayanan Terpadu Satu Pintu Kanwil Kemenag Provinsi Jambi - Alvionita, Erica; Siahaan, Kondar (Jurnal Manajemen Sistem Informasi, 2021)
The permit process that runs at the PTSP Regional Office of the Ministry of Religion still requires applicants to come directly to the One Stop Integrated Service Office of the Ministry of Religion to be able to process the permit, starting from taking queue numbers, filling in forms and manually inputting files to available counters. This process is deemed not fulfilling the service objectives of the One Stop Integrated Service at the Jambi Provincial Office of the Ministry of Religion which aims to simplify service procedures at the Regional Office of the Ministry of Religion of Jambi Province and is less effective for applicants who have the complexity of attending in person because there is no online registration option, therefore A system is needed that can assist applicants / the community in licensing arrangements and online file monitoring functions. The purpose of this research is to be used by the Ministry of Religion Regional Office and licensing applicants in facilitating the process of managing permit letters. This system is designed using Unified object-based modeling techniques. Modeling Language (UML) in the form of use case diagrams, activity diagrams, and class diagrams. The output of this research is a prototype design of the Licensing Service Information System at the PTSP Kanwil Kemenag Jambi Province.